Effects of organic manures on the growth and yield of malabar nut (Justicia adhatoda L.) (Dhaka University Journal of Biological Sciences, 2021)
A pot (7 kg soil/pot) experiment was carried out to evaluate the growth performance of malabar nut (Justicia adhatoda L.) as influenced by different organic manures. Manures were (a) ACI, (b) FDA, (c) GTS, (d) Green life, (e) Kaji, (f) Majim, (g) Shebok, (h) Shufola, (i) Cowdung, and (j) Water hyacinth, applied at the rate of 10 ton/ha. There were eleven treatments and three replications. Pots were arranged in a completely randomized design (CRD). To evaluate the growth performance viz. height, leaf number, leaf area, and leaf area index, girth, and branches were recorded at 15 d intervals up to harvest. Plants (90 d old) were harvested as root, stem, and leaf. Fresh and dry weights of root, stem, and leaf were recorded. The highest height (80.90 cm), leaf number (28.70 no./plant), leaf area (175.77cm2/plant), leaf area index (0.462) were observed in water hyacinth. The lowest height (42.20 cm), leaf number (13.70 no./plant), leaf area (45.58 cm2/plant), and leaf area index (0.12) were recorded in control. Maximum fresh and dry weights (root, stem, and leaf) were 129.19 g/plant and 57.97 g/plant found in water hyacinth, respectively. Results concluded that the overall growth and yield were achieved better in water hyacinth manure.Dhaka Univ. J. Biol. Sci. 30(1): 79-86, 2021 (January)